Employee disengagement from the perspective of frontline employees: a hotel case study in Zimbabwe - Moment Bhebhe (Management College of Southern Africa (MANCOSA), 2022)
Employee disengagement in the hotel industry is deepening, with profound impacts on customer service delivery. However, there is scant empirical evidence focusing on employment and human resource management in the hotel industry, particularly predicated on the perceptions of employees. This study examines employee disengagement from the perspective of employees in a selected hotel organisation. More particularly, it focuses on frontline employees, whose jobs involve daily service encounters with clients. Frontline employees are central to customer satisfaction. Gaining insights from the viewpoint of these employees can help enlighten both management and human resources practitioners in formulating and implementing appropriate strategies that can help mitigate employee disengagement. The study followed a qualitative case study approach using a sample of 30 participants, drawn from frontline service departments, including frontline service managers and a human resource management representative. Data was collected using two focus group discussions with frontline employees and 9 semi-structured interviews with management. A thematic approach was utilised to analyse data. Findings reveal that frontline employees regard management behaviour as the major factor to their disengagement. When managers, particularly those in frontline service departments, become unappreciative of employee effort, do not appear to be supportive or engage in unfair assessments, the behaviour of frontline employees becomes evident to clients, in the form of a lack of promptness in serving clients, poor food preparation and failure to keep a constant smile during service encounters. Management efforts to mitigate the disengagement of frontline employees is essential in creating sustain able and positive customer experiences in the hotel business.